Ultra‐low cycle torsion fatigue of annealed copper. Issue 12 (26th May 2015) - Hofmann, U.; Riedle, J.; Altenberger, I.; Cote, A.; Burwell, M.
ABSTRACT: Torsion experiments show that pure annealed copper is able to withstand very high plastic strain amplitudes when it is loaded cyclically with less than 30 cycles to failure. Under these ultra‐low cycle fatigue conditions, the performance of copper is significantly better than that of the annealed steels A36 and AISI 304, which were also tested in this study for comparison. The dependence of fatigue life on strain range can be described by a power law. In the case of an initial overloading, fatigue life can be estimated using the Palmgren–Miner rule. The long low cycle fatigue life of copper is explained by a thermally activated softening mechanism which takes place while the material heats up as a result of the cyclically repeated plastic deformation. The softening is accompanied by a change in microstructure. The low cycle fatigue properties of copper can be utilized for designing hysteretic dampers for seismic protection.